Estudio de problemáticas que afectan las operaciones de los puertos de Buenaventura, para la agilización del comercio exterior (2020)
The objective of this degree project is to analyze the problems that affect the loading and unloading of containers in the ports of Buenaventura to streamline foreign trade. At a methodological level, a descriptive study with a mixed approach is used, where qualitative and quantitative information is used to address the problems of said port. Regarding techniques for data collection, documentary review is used, from secondary sources such as academic studies and reports from official entities. Regarding the problems that affect loading and unloading activities, it is evident that complex and demanding processes have been established in efforts and resources that lead to delays. Similarly, there are problems in the access roads to the port that generate high costs such as risks for the mobilization of cargo to and from Buenaventura. The strategies focused on improving the efficiency and competitiveness of the Port of Buenaventura should focus on three macro aspects; improve access roads from the center of the country, increase capacity and infrastructure, strengthen the efficiency of administrative management processes such as documentation of the merchandise. In all three aspects, the entities in charge of the issue have been making efforts, however, it is concluded that greater speed is necessary in the execution of the works, in particular of the roads that allow the mobilization of goods from the center of the country, in addition to the monitoring and surveillance of the control entities to ensure compliance with the commitments derived from the contracts entered into, such as their execution time and costs.